Mexico : Staff Report for the 2012 Article IV Consultation. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2012)
The IMF staff report on Mexico's financial policies has been satisfactory; these policies have been said to act as a buffer against risks that erupted during the global economic crisis. Mexico has been identified as a prudent and fairly well-managed economy. However, the issues that would pose a challenge to the financial sector and would hamper overall economic stability of the country were emphasized, and certain key areas that need attention on a priority basis were highlighted.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet